2012
DOI: 10.1080/10286020.2012.684683
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cell cycle arrest by GL331 via triggering an ATM-dependent DNA damage response in HepG2 cells

Abstract: GL331, a topoisomerase II inhibitor, has been found to trigger DNA damage response (DDR) to induce cell cycle arrest. However, the underlying mechanism has not yet been fully understood. This study investigated the molecular mechanism involved in the GL331-induced cell cycle arrest via DDR in human hepatocellular carcinoma HepG2 cells. As a result, GL331 could induce S arrest and up-regulate the phosphorylation of the histone H2AX variant (γ-H2AX). Ataxia telangiectasia mutated protein kinase (ATM) was activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These studies raised a question: which is a better strategy, to activate or to inhibit ATM activity, in treating HCC patients? Recently, Wang et al revealed that GL331, a topoisomerase II inhibitor, activates autophosphorylation of ATM at S1981 and extends activations of DNA damage signaling pathways including TP53/p21 and Chk2/Cdc25A cascades to reach S phase arrest in HepG2 cells (Table 1) [146]. A small molecular inhibitor, CGK733, which targets kinase activity of ATM, can obviously reverse the resistance of HepG2 to taxol treatment (Tables 1 and 3) [147].…”
Section: The Impact Of Ddr Pathways On Hcc Developmentmentioning
confidence: 99%
“…These studies raised a question: which is a better strategy, to activate or to inhibit ATM activity, in treating HCC patients? Recently, Wang et al revealed that GL331, a topoisomerase II inhibitor, activates autophosphorylation of ATM at S1981 and extends activations of DNA damage signaling pathways including TP53/p21 and Chk2/Cdc25A cascades to reach S phase arrest in HepG2 cells (Table 1) [146]. A small molecular inhibitor, CGK733, which targets kinase activity of ATM, can obviously reverse the resistance of HepG2 to taxol treatment (Tables 1 and 3) [147].…”
Section: The Impact Of Ddr Pathways On Hcc Developmentmentioning
confidence: 99%
“…Cell viability was assessed with MTT assay as previously described. 27 Various concentrations of CHB were added into wells and incubated for 72 hours. IC 50 value was defined as the drug concentration that inhibits 50% cell growth compared with the untreated controls and was calculated by Graphpad Prism 6.0 software.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was carried out as described previously. 27 The membrane was immunoblotted with mouse monoclonal antibody to caspase 3 (1:1,000), caspase 9 (1:500), mouse monoclonal antibody to Bax and Bcl-2 (1:500), rabbit polyclonal to Fas and FasL (1:500), rabbit polyclonal to β-actin (1:1,000), rabbit polyclonal to AIF (1:500) (Santa Cruz Biotechnology, Santa Cruz, CA, USA), rabbit polyclonal to active capase 3 (1:1,000) (CST, Danvers, MA, USA), rabbit polyclonal to capase 8 (1:1,000), and rabbit polyclonal antibody to cytochrome c (1:500) (Bioworld Technology Inc., Nanjing, People’s Republic of China). The membranes were finally developed using enhanced chemiluminescence (Fuji Film, Tokyo, Japan) reagent (Applygen Technologies Inc.) and exposed to film according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%